HOLISTIC GEOTOURISM AS A CATALYST FOR TOURISM DEVELOPMENT IN NORTH SULAWESI: ANALYSIS AND IMPLEMENTATION STRATEGIES: Geotourism Holistik sebagai Katalis Pembangunan Pariwisata Sulawesi Utara: Analisis dan Strategi Implementasi - Harley Mangindaan (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study investigates the disparities and opportunities within the tourism sector of North Sulawesi, Indonesia, with a focus on developing a holistic and sustainable geotourism strategy. Employing a mixed-methods approach, the research integrates quantitative data (descriptive analysis, t-tests, and linear regression) to identify key imbalances, such as fluctuating tourist arrivals, perception gaps between domestic and international tourists regarding accommodation and transportation quality, and factors influencing tourist satisfaction (attraction quality, service quality, and infrastructure). Qualitative data, gathered through in-depth interviews and participatory observation, provides deeper insights into the causes of these imbalances, including discrepancies between destination managers' perceptions and tourist expectations, lack of coordination among stakeholders, limited human resource capacity, and minimal local community involvement. The research proposes geotourism as a viable strategy to bridge these gaps and foster sustainable tourism development. Geotourism, in this context, is defined beyond mere geological promotion; it encompasses a holistic approach rooted in local wisdom, environmental preservation, and community empowerment. Key elements of this strategy include developing geotourism-based products, enhancing service quality and infrastructure, increasing local community participation, implementing effective promotion, and ensuring sustainable management practices. The study adheres to ethical research principles, including informed consent and data confidentiality. The findings offer valuable insights for policymakers and stakeholders, providing a framework for developing a more resilient, inclusive, and sustainable tourism sector in North Sulawesi. By embracing geotourism principles, North Sulawesi can leverage its unique geological, biological, and cultural assets to create a thriving tourism industry that benefits both the environment and local communities.